Pengaruh Sikap dan Dukungan Keluarga terhadap Kelengkapan Imunisasi Dasar Bayi di Papua: Tantangan dan Strategi Peningkatan - Aminuddin, Suci Pratiwi (ANWARUL, 2025)
This study examines the impact of family attitudes and support on the completeness of basic immunization for infants in Papua. The findings reveal that Papua’s immunization coverage of only 55.3% is far below the national average of 84.2%, indicating significant challenges. Geographic, cultural, and socioeconomic barriers hinder access to immunization services. Positive family attitudes and strong emotional support significantly increase immunization completeness, while distrust in vaccines and limited access remain obstacles. Community-based interventions, the involvement of cultural leaders, and the use of innovative technologies like drones are crucial strategies. This research underscores the importance of a holistic approach involving government, healthcare workers, and local communities to achieve equitable and effective immunization programs in Papua.